The European Union as recently seen by two Italian economists - Giacomo Costa (Rosenberg & Sellier, 2015)
This is a review of the books on the European Union by two well-known Italian economists, Luigi Zingales and Giacomo Vaciago. It turns out there is a broad area of agreement and complementarity between them. Their treatments are summarized under the following ten headings: 1) The political genesis of the European Union; 2) the surprisingly narrow range of activities included in the present economic and monetary union; 3) the dubious validity of the “theory of forward reactions”, that should guarantee the forward direction of the unification process; 4) The unsure presuppositions of the Maastricht Treaty, and the reasons why it arose the skepticism of most American economists; 5) the Italian crisis and the European paralysis; 6) Italy stands to Europe as Southern Italy to Italy; 7) Italexit? 8) What brakes the progress of the unification process? 9) What corrections to existing institutions? 10) Is there still a role for a European Federation?